The attitude of the female students of medical and non-medical fields of studies towards the cervical cancer prophylaxis - Olejniczak, Dominik; Bień, Magdalena (Medical Studies/Studia Medyczne, 2014)
Introduction: The mortality of women with cervical cancer is one of the main problems of oncology. Poland is a country with high morbidity and mortality for this type of malignancy. In 2007, the incidence was 11.8 and the mortality was 5.0 per 100.000. Despite the availability of free Pap tests and many prevention campaigns, the incidence in Poland has remained at a constantly high level for several years. This prompted us to examine the degree of knowledge of different groups of the population about prophylaxis Aim of the research: To determine the knowledge and attitudes of students towards the prevention of cervical cancer. Material and methods: The study group are students of medical and non-medical faculties, who in total accounted for a panel of 112 people. The study was conducted at two universities: the Medical University of Warsaw and Kielce University of Technology. The diagnostic survey method: the study took the form of an anonymous questionnaire consisting of 25 closed questions on cervical cancer and its prevention. To determine whether there is a relationship between the subsidiaries, we used statistical methods such as test compliance χ 2 for a confidence level of p = 0.05, and r-Pearson’s correlation coefficient. Results: Training in the medical school is associated with having more knowledge in the field of medicine. Conclusions: Although the respondents most frequently declared that the main reason for them reporting to a gynaecologist was for regular check-ups, the percentage of the response was insufficient to conclude that students appreciate the role of secondary prevention of cervical cancer.